2017
DOI: 10.1097/aog.0000000000002048
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Planned Cesarean Delivery and Neonatal Mortality and Morbidity in Twin Pregnancies

Abstract: Planned vaginal delivery for twin pregnancies with a cephalic first twin at or after 32 weeks of gestation was associated with low composite neonatal mortality and morbidity. Moreover, planned cesarean compared with planned vaginal delivery before 37 weeks of gestation might be associated with increased composite neonatal mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 21 publications
(29 reference statements)
4
63
0
2
Order By: Relevance
“…However, the Twin Birth Study in 2013 reported that there were no significant benefits in planned CS for uncomplicated twins pregnancies 43 . The JUMODA study confirmed that planned CS (compared with planned vaginal delivery) for twins could be associated with increased composite neonatal mortality and morbidity, particularly when delivery was before 37 weeks 44 . Nevertheless, there is a strong preference among mothers with twin pregnancies for planned CS, which is likely to be compounded by the clinician's lack of confidence in conducting complex vaginal deliveries 45 .…”
Section: Category 8 (Multiple Pregnancies)mentioning
confidence: 84%
“…However, the Twin Birth Study in 2013 reported that there were no significant benefits in planned CS for uncomplicated twins pregnancies 43 . The JUMODA study confirmed that planned CS (compared with planned vaginal delivery) for twins could be associated with increased composite neonatal mortality and morbidity, particularly when delivery was before 37 weeks 44 . Nevertheless, there is a strong preference among mothers with twin pregnancies for planned CS, which is likely to be compounded by the clinician's lack of confidence in conducting complex vaginal deliveries 45 .…”
Section: Category 8 (Multiple Pregnancies)mentioning
confidence: 84%
“…The national, observational, prospective, population-based cohort study of the mode of delivery of twin pregnancies (JUMODA: JUmeaux MODe d' Accouchement) conducted by Schmitz et al 4 , took place in France from 10 February, 2014, through 1 March, 2015. All French maternity units performing more than 1,500 annual deliveries were invited to participate, and 176 of the 191 eligible units (92%) agreed.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information about the participating women and maternity units has been reported by Schmitz et al 4 . Briefly, this cohort was specially designed to assess the effect of the mode of delivery on neonatal and maternal outcomes in twin pregnancies at or after 22 weeks of gestation (N = 8,823 women included).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations